2003
DOI: 10.1051/0004-6361:20030382
|View full text |Cite
|
Sign up to set email alerts
|

The VLA-VIRMOS Deep Field

Abstract: Abstract.We have conducted a deep survey (rms noise 17 µJy) with the Very Large Array (VLA) at 1.4 GHz, with a resolution of 6 arcsec, of a 1 deg 2 region included in the VIRMOS VLT Deep Survey. In the same field we already have multiband photometry down to I AB = 25, and spectroscopic observations will be obtained during the VIRMOS VLT survey. The homogeneous sensitivity over the whole field has allowed to derive a complete sample of 1054 radio sources (5σ limit). We give a detailed description of the data re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
215
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 148 publications
(223 citation statements)
references
References 24 publications
7
215
1
Order By: Relevance
“…The extension of a radio source increases its total flux density when compared to its peak surface brightness, however, background noise can lower the total flux density (see Bondi et al 2003). Therefore, in Fig.…”
Section: Resolved Versus Unresolved Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extension of a radio source increases its total flux density when compared to its peak surface brightness, however, background noise can lower the total flux density (see Bondi et al 2003). Therefore, in Fig.…”
Section: Resolved Versus Unresolved Sourcesmentioning
confidence: 99%
“…In recent decades, radio interferometers, such as the Karl G. Jansky Very Large Array (VLA), Australia Telescope Compact Array (ATCA), and Giant Meterwave Radio Telescope (GMRT), have surveyed fields of different sizes (ranging from tens of square arcminutes to thousands of square degrees), depths (microjansky to jansky), and multiwavelength coverage (e.g., Becker et al 1995;Condon et al 1998Condon et al , 2003Condon et al , 2012Ciliegi et al 1999;Georgakakis et al 1999;Bock et al 1999;Prandoni et al 2001;Hopkins et al 2003;Schinnerer et al 2004;Bondi et al 2003Bondi et al , 2007Norris et al 2005;Schinnerer et al 2007Schinnerer et al , 2010; Afonso et al 2005;Tasse et al 2007;Smolčić et al 2008Smolčić et al , 2014Owen & Morrison 2008;Miller et al 2008Miller et al , 2013Owen et al 2009;Hales et al 2014). These past surveys have shown that deep observations at high angular resolution ( 1 ) with exquisite panchromatic coverage are critical to comprehensively study the radio properties of the main galaxy populations, avoiding cosmic variance with large area coverage (e.g., Padovani et al 2009;Padovani 2011;Smolčić et al 2008Smolčić et al , 2009bSmolčić 2009;Smolčić & Riechers 2011;Seymour et al 2008;Bonzini et al 2012Bonzini et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Bondi et al 2003). We employed the aips task sad on both the mosaic image and the noise image to obtain a catalogue of candidate sources above the threshold of 4.5σ.…”
Section: Source Cataloguementioning
confidence: 99%
“…Radio observations of the CFHTLS-D1 field were taken at 1.4 GHz and 610 MHz from the Very Large Array (VLA, B-Array) and the Giant Metrewave Radio Telescope (GMRT), respectively, as part of the VLT-VIRMOS survey (Bondi et al 2003). Details of the observations and reduction of the VLA data are given in Ciliegi et al (2005) and those of the GMRT data are given in Bondi et al (2007).…”
Section: Other Ancillary Datamentioning
confidence: 99%